Dietary Flavonoids as Therapeutics for Preterm Birth: Luteolin and Kaempferol Suppress Inflammation in Human Gestational Tissues In Vitro. (5th June 2013) - Wall, Courtney; Lim, Ratana; Poljak, Marin; Lappas, Martha
Abstract : Infection/inflammation is commonly associated with preterm birth (PTB), initiating uterine contractions and rupture of fetal membranes. Proinflammatory cytokines induce matrix metalloproteinases (MMPs) that degrade the extracellular matrix (ECM) and prostaglandins which initiate uterine contractions. Nuclear factor- κ B (NF- κ B) and activator-protein- (AP-)1 have key roles in the formation of these prolabour mediators. In nongestational tissues, dietary flavonoids such as luteolin and kaempferol inhibit NF- κ B, AP-1, and their downstream targets. The aim of this study was to determine if luteolin and kaempferol reduce infection-induced prolabour mediators in human gestational tissues. Fetal membranes were incubated with LPS, and primary amnion cells and myometrial cells were incubated with IL-1 β in the absence or presence of luteolin or kaempferol. Luteolin and kaempferol significantly reduced LPS-induced secretion of proinflammatory cytokines (IL-6 and IL-8) and prostaglandins (PGE2 and PGF2 α ) in fetal membranes, IL-1 β -induced COX-2 gene expression and prostaglandin production in myometrium, and IL-1 β -induced MMP-9 activity in amnion and myometrial cells. Luteolin and kaempferol decreased IL-1 β -induced NF- κ B p65 DNA binding activity and nuclear c-Jun expression. In conclusion, luteolin and kaempferol inhibit prolabour mediators in human gestational tissues. Given the central role of inflammation in provoking preterm labour, phytophenols may be a therapeutic approach to reduce the incidence of PTB.